2021
DOI: 10.1261/rna.078962.121
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and initial characterization of YloC, a novel endoribonuclease in Bacillus subtilis

Abstract: Bacillus subtilis genome is predicted to encode numerous ribonucleases, including four 3’ exoribonucleases that have been characterized to some extent. A strain containing gene knockouts of all four known 3’ exoribonucleases is viable, suggesting that one or more additional RNases remain to be discovered. A protein extract from the quadruple RNase mutant strain was fractionated and RNase activity was followed, resulting in identification of an enzyme activity catalyzed by the YloC protein. YloC is an endori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The E. coli homologue protein of YloC is YicC, which shares 30% sequence identity with the former. In vitro studies showed that YicC performed a similar function to that of YloC but with a slower cleavage rate …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The E. coli homologue protein of YloC is YicC, which shares 30% sequence identity with the former. In vitro studies showed that YicC performed a similar function to that of YloC but with a slower cleavage rate …”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies showed that YicC performed a similar function to that of YloC but with a slower cleavage rate. 7 YicC is a member of the highly conserved "UPF0701 protein family" (Uncharacterized Protein Family 0701), which contains two other founding members: Bacillus subtilis YloC and Haemophilus inf luenzae HI_0467. UPF0701 proteins comprise the N-terminal domain (YicC_ N) and the Cterminal domain (DUF1732; Domain of Unknown Function 1732), and the functions of both domains are obscure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The positions of the three arginines required for DNA binding by RemA [49] . yloC (dark grey) encodes for an endonuclease, [120] gmk (green) encodes for guanylate kinase converting GMP into GDP in an ATP-consuming manner, [118] and rpoZ (light grey) encodes for the omega subunit of the RNA polymerase. [119] binding sites for RemA and SinR localize upstream of the −35 box of the σ A -type PepsA promoter, the positions of two of the SinR binding sites are found downstream of the −10 box at PtapA.…”
Section: Integration Of Rema Into the Transcriptional Regulatory Circ...mentioning
confidence: 99%
“…(D) Organismic distribution and genetic neighborhood of remA (blue). yloC (dark grey) encodes for an endonuclease, [ 120 ] gmk (green) encodes for guanylate kinase converting GMP into GDP in an ATP‐consuming manner, [ 118 ] and rpoZ (light grey) encodes for the omega subunit of the RNA polymerase. [ 119 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition to RNase Y, RNase III has been suggested to cleave in dozens of mRNAs, potentially initiating decay for a subset of the transcriptome (DiChiara et al, 2016). As new endoribonucleases are discovered, additional enzymes may also be implicated in decay-initiating events across the transcriptome (Cerullo et al, 2022; Ingle et al, 2022; Leroy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%